Information System Strategic Planning in PT XYZ Using Wetherbe's Methodology - Andi Sulistiawan; Melkior Nikolar Ngalumsine Sitokdana (Politeknik Pertanian Negeri Samarinda, 2020)
Along with the development of technology in business, PT XYZ, which is engaged in the food industry, which is located in Sidomukti, Salatiga City is required to be adaptive and innovative by utilizing the availability of information technology. In order to win the competition, and information system strategic plan is needed to support the implementation of information technology and information systems in terms of operations as well as for strategic ones. Therefore, this research conducted by making strategic planning of information systems for use at PT XYZ using the Wetherbe methodology. This methodology is considered as an appropriate approach tool for the company. The solution for information system requirements is based on the strategic planning analysis that has been carried out, namely, producing nine information systems consisting of one information system to be developed from existing applications and eight information systems for the proposed application. And IT personnel are needed for the database and network server work or to carry out proper training for each employee so that if there is damage to the system and infrastructure it can be directly handled. This was done due to the condition of the number of human resources and limited funds for the strategic planning of information systems.